Robot Line Maze Pencari Jalur Tercepat - Robby Pranata; Retno Tri Wahyuni; Tianur tianur (Jurnal SISKOM-KB (Sistem Komputer dan Kecerdasan Buatan), 2018)
Robot line maze is a robot designed to move with the aid of autonomous sensor to follow a line with a certain pattern. Stripe pattern used is black that is placed on a white surface that is detected by the color sensor. This robot but to follow the flow of the line, also can find the shortest route to reach the target of the starting position to the finish. This maze robot line uses 2 priority is the priority right and left. Left to priority, when the robot will give priority to meet the robot intersection turn left rather than straight or turn right, if it is not found then the robot option left turn will take a straight path. Likewise for the right of priority, when the robot will give priority to meet the robot intersection turn right rather than straight or turn left, when it is not found then the robot turn right choice will take a straight path. Thus, the time required to reach the destination in a maze path more quickly and effectively. At the end of the project is to design and realization of the design of the robot line maze using ATMega8535 AVR microcontroller, sensors photodiode as sensor lines, as LCDdisplays, DC motors as well as the robot driver using Bascom AVR programming language